(untitled) (Journal of the College of Basic Education, 2022)
This study tends to shed light on the experience of virgin love among pre-Islamic poets who wrote about the beloved woman in their poetry, especially the owners of the ten pendants. . This study relied on an analytical textual approach that examines the discourse based on its internal determinants